Insights into the Relationship between Intestinal Microbiota of the Aquaculture Worm Sipunculus nudus and Surrounding Sediments - Junwei Li; Suwen Chen; Peng Wu; Changbo Zhu; Ruiping Hu; Ting Li; Yongjian Guo (Fishes, 2023)
Sipunculus nudus is an important intertidal aquaculture species that can ingest organic matter from the surface sediment and shows a high transportation capacity in sediment. However, little is known about the influence of intertidal aquaculture species on the sediment microbial community and the exchange of microbiota between the intestine and the surrounding sediment. In this study, the microbial communities in the intestine of S. nudus and three kinds of surrounding sediments were analyzed using high-throughput sequencing of the 16S rRNA gene amplicon, and the relationships between different communities were examined. Principal coordinate analysis and ANOSIM/Adonis analysis showed that the microbial communities of worm intestine samples were significantly different from those of surrounding sediments (p < 0.05). Meanwhile, compared with the sediment samples, the microbial α-diversity was significantly lower in the intestinal samples. Although the relative abundances of Proteobacteria and Cyanobacteria were high in all samples, three phyla (Bacteroidetes, Gemmatimonadetes, and Latescibacteria) showed a great difference between the four groups, as the abundances of the three phyla were significantly lower in the intestinal samples. Moreover, several microbial interactions were found between the worm intestine and surrounding sediments. BugBase functional prediction analysis indicated that the oxygen status of the sediment and the intestine was changed by bioturbation by the worm. Therefore, the microenvironment and microbial community in sediment were affected by the activity of S. nudus in the intertidal aquaculture zone.